Acute and short-term effect of verapamil on cardiac and peripheral hemodynamics and on left ventricular diastolic function in essential hypertension - Isik, A.; Luleci, C.; Donder, E.; Eren, O.; Celebi, H.; Arslan, N. (My University, 1993)
[Abstract Not Available]
Keywords: verapamil; aged; article; clinical article; electrocardiogram; essential hypertension; heart function; human; intravenous drug administration